Report on research, innovation and technological performance in Germany 2019 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2019)
[Foreword] After a delayed start, the Federal Government has presented numerous plans for research and innovation policy in the new legislative period. The Commission of Experts comments on some of the most significant plans in chapter A 1. In the new High-Tech Strategy 2025, the Federal Government has once again committed itself to the target of spending 3.5 percent of gross domestic product on R&D by 2025. However, the funds currently budgeted are not sufficient to meet this target. The Commission of Experts therefore once again calls for the introduction of tax-based support for R&D, focused on SMEs. It also recommends that the Federal Government grants considerable freedom to the proposed Agency for Disruptive Innovations. Unless it is granted independence from political control, the agency will be unable to meet the expectations placed upon it. The Federal Government's Artificial Intelligence Strategy (chapter A 2) documents the high regard in which it holds this field of research. The funding volume of exteuro3 billion (by 2025) appears to be appropriate. The current version of the AI Strategy, however, remains vague on numerous points and must be substantiated without delay. The Commission of Experts expressly warns against adopting a scatter-gun approach to research funding. However, the Commission of Experts considers a wide-ranging transfer of knowledge to be necessary. It supports the systematic expansion of European collaborations so that, as part of the association of EU partner countries, Germany can keep pace with the USA and China as the leading nations in the field of AI research. In chapter A 3, the Commission of Experts examines the funding structures implemented by the German Research Foundation (Deutsche Forschungsgemeinschaft, DFG), Germany's largest research funding organization, and compares them with those of key research funding organizations in the United Kingdom, the Netherlands, Switzerland and the USA. This examination shows that the DFG places strong emphasis on funding programmes intended to foster collaboration and structural development. It also highlights that the average funding provided by the DFG for new single project applications is comparatively low, and the average funding duration relatively short. The Commission of Experts suggests that a review be conducted to examine whether the high weighting given to structural funding formats should be adjusted in favour of single project funding. In chapter B 1, the Commission of Experts acknowledges the importance of start-ups in the innovation system. In Germany, a vibrant start-up scene has developed in recent years that is highly concentrated in regional terms. To promote globally visible start-up ecosystems, it is important not to counteract this geographical concentration but, instead, to expand existing and emerging ecosystems. Start-ups in Germany - particularly those in the growth phase - still have problems in accessing sufficient venture capital. With this in mind, the conditions for private investments in start-ups must be further improved; in particular, incentives should be created to encourage institutional investors to invest more heavily in start-ups. In chapter B 2, the Commission of Experts investigates the contribution that research and innovation policy can make to the energy transition. Important innovative technologies and business models for decarbonisation of the German energy system are already market-ready, or will be so in the near future. However, their diffusion is hampered by CO2 prices set too low as well as by regulatory requirements. In order to remove these barriers, taxes and levies on energy across all sectors of the economy should be geared to the damage energy sources inflict on the environment or to their CO2 content. To avoid putting the success of the energy transition at risk, political actors should structure potential reforms in a socially sustainable manner - without curtailing the steering effect of climate-protection measures. In chapter B 3, the Commission of Experts discusses blockchain technologies, which provide an immutable, forgery-proof way to store and transfer digital data. Germany is well positioned to exploit the economic and social potential of such technologies. However, it is important to promote the use and further development of blockchain technologies with a flexible regulatory framework, such as by setting up regulatory test beds. It will also be necessary to develop skills and knowledge in society and administration in order to reliably assess the opportunities and risks involved in the use of these technologies. In chapter B 4, the Commission of Experts analyses the digitalization of German tertiary education (TE) institutions. The German TE institutions surveyed ascribe a high level of importance to digitalization, but this is yet to be reflected in the level of digitalization achieved. The Commission of Experts therefore considers there to be significant potential for development, especially in the areas of teaching and administration. The governance structures currently in place in TE institutions hamper the progress of the digitalization process. To ensure that digitalization can succeed on the whole, TE institutions must continue to modernize their administration. The Commission of Experts recommends supporting TE institutions in this process by introducing a lump-sum digitalization payment. [...]
Keywords: 330